Empowerment Of Catfish Farming Group Towards Food Security In Mojorang Agung Village Wondayu Sidoarjo - Sutrisno; Hervina Puspitosari; Rohmatul Faizah (Fakultas Hukum, UPN Veteran Jawa Timur, 2021)
The village is one of the villages in the Wonoayu sub-district which has the potential for the development of catfish farming business, due to the availability of adequate land both in the yard and outside the yard, the water source is available continuously. both river water and groundwater. The most important problem is that the legality of fish cultivator groups for the development of fish farming activities in Pokdakan Mina Mojo, Mojorangagung Village, Wonoayu District, Sidoarjo Regency does not yet exist and is the strong desire of the group so that it is time to be appointed as one of the advantages of villages in the fisheries sector as an effort to realize resilience. food, which in turn can increase the economy, income, and welfare of the village of Mojorangagung, Wonoayu District, Sidoarjo Regency. Empowerment activities are also through the capacity building through training and mentoring for catfish farming groups as well as various innovations that can be developed through processed catfish products such as processed catfish smoked fish products, catfish processed in shredded packaging as well as various products and other innovations. which can be circulated in various areas including the utilization of waste that can be made as catfish feed. The problem that is often faced by catfish farmers is in marketing. Marketing needs attention in assisting catfish cultivation in addition to the importance of legal aspects, ranging from processed variations, packaging that can attract consumers' purchasing power and become food products that are delicious and safe for consumption. Technological assistance is very much needed in developing the productivity of processed catfish so that it can be diverse so that it further expands the market in marketing processed catfish products.